Strategi Pembelajaran Efektif Guru PAI dalam Mengatasi Kesulitan Belajar di SMPN 3 Grogol - Amanda Oktavia Safitri; Triono Ali Mustofa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
PAI plays an important role in the school curriculum that serves to shape students' character, morals, and spirituality. However, teachers are often faced with student learning difficulties. PAI teachers need to have effective learning strategies to help students overcome learning difficulties. This study aims to analyze teacher strategies, implement strategies and classify internal and external factors in experiencing learning difficulties. This study used qualitative research through a phenomenological approach. Data collection was carried out through observation, interviews and documentation. Observation was carried out at SMPN 3 Grogol Sukoharjo. Data analysis techniques used qualitative data analysis, namely data reduction, data presentation, and drawing conclusions. Based on the results of interviews with PAI teachers, there are still many students who are less motivated to take lessons and many students experience learning difficulties. Difficulties experienced in terms of process, material for reading and writing Al-Qur'an verses and expertise in memorization. PAI teachers must have effective learning strategies in overcoming student learning difficulties, namely 1). approaching students, 2). applying interactive learning methods, 3). coaching students through the rohis program, and 4). carrying out evaluations. Internal factors that affect student learning difficulties are: 1). low interest in learning the PAI subject, 2). low student motivation, 3). low ability to read, write and memorize the Qur'an. External factors include: 1). learning methods and media that are not in accordance with student characters, 2). parents pay less attention to their children, 3). excessive use of technology.